Intensity and extent of adopting watershed activities in Nagaland - YADAV, MUKESH KUMAR; SHARMA, AMOD; SINGH, PARMINDER (The Indian Journal of Agricultural Sciences, 2021)
In India, agriculture is important occupation of which 52.00% of the people depend for their livelihood. For the present study a multistage random sampling technique is adopted with a total of 320 respondents selected from the Kohima and Dimapur district of Nagaland state, among that 160 farmers are beneficiaries and 160 are non-beneficiaries both drawn from the watershed villages as check farmers for assessing the impact of watershed on sustainability of the agriculture during the agricultural year 2018-20. The Regression analysis results reveal that the farmer's enrollment as member in watershed programme increases about 1.65 % in the agricultural income, while the regression coefficient of education level for the medium farmers was found to be 0.76 implying that 1.00% increases in the educational level yields with 0.76% on their agricultural income. However, it is non-significant for small and large farmers; the results reveal that family size of the respondents positively influence the adoption of livestock, soil and water conservation and compost and agro-forestry at 5.00% level of significance. The tetra correlations results showed that watershed management practices are positively correlated and practices the activities in jointly or complementary to each other. All the positive impacts of watershed development programme are expected to improve standard of living at the household level, establishing financial framework for sustainable functioning of watershed projects and participatory planning for upliftment of the people and conserving the biodiversity which is another prerequisite for ensuring the sustainability of the watershed project.